The Community Partnership Program at UMKM Puncak Sejahtera Bukit Aren Village through Mentoring and Development of Virgin Coconut Oil (VCO) and Gula Aren Products - Yuszda K. Salimi; Lisna Ahmad; Melizubaida Mahmud (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
UMKM Puncak Sejahtera are micro, small and medium enterprises that produce virgin coconut oil (VCO) and palm sugar which are faced with production and marketing problems. The problems faced from the production aspect are that the product is still limited, does not have technological skills innovation, good product packaging and storage, does not have a machine with a large capacity and produces good quality. The problem from another aspect is not having extensive business management and marketing capabilities so that financially the results obtained are insufficient for daily needs. Even though the potential of coconut and palm sugar can be developed various products with a fairly high economic value. The community partnership program (PKM) aims to help and develop VCO and palm sugar businesses in UMKM Puncak Sejahtera. VCO manufacturing innovation training has been carried out with several methods and has been tested in the laboratory, assistance in processing technology for coconut and palm sugar-based product innovations, VCO training and palm sugar business management through packaging technology, design labeling techniques, storage time and marketing. Business license assistance for business development and online marketing is also carried out in this program. The methods used are the RRA (Rapid Rural Appresial) and PRA (Participatory Rural Appresial) approaches, including: 1) priority of problems to be addressed, 2) training and assistance based on problems in stages, 3) product improvements are carried out based on the results of laboratory tests. The result of this activity is an increase in understanding, skills of members of the UMKM Puncak Sejahtera group in Bukit Aren village in processing VCO and palm sugar with good quality and quantity of production. VCO products and cooking oil are certified for nutritional value in the laboratory. Product marketing is expanded online to make it easier to sell products.